Metodología para la selección de modelos hidrodinámicos – Caso de aplicación: variabilidad espacial de la estructura térmica en el embalse tropical Riogrande II, Colombia. (2016)
This article presents a methodology for a guided selection of a hydrodynamic model to study physical processes in a reservoir. It is based on both qualitative and quantitative criteria that are applied in order to study the spatial variability of the thermal structure in the Riogrande II tropical reservoir. The method consists of three main stages: i) definition and search, ii) pre-selection, and iii) selection. As a result, the DELFT3D and MIKE3 models were implemented, and the simulated temperature profiles were compared to field data that was collected between March 23rd and 27th, 2010. ELCOM was defined as a reference model, and the time series of the thermocline depth, the mixing layer depth, and its average temperature were compared with the selected models. The final selection was supported by using three different statistical parameters: the index of agreement (d1), the MAE, and the RMSE. The quantitative analysis showed that the DELFT3D model behaves better than MIKE 3.